(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new genus name Hispaniococcus is described for Ovaticoccus agenjoi (Gomez-Menor, 1954) species on Artemisia sp. from Spain. A new species, Pseudochermes williamsi is described from the Palaearctic Region, on Coffea arabica from Canary Island. The morphological relationship of Borchseniococcus, Calycicoccus, Cryptococcus, Kuwanina, Ovaticoccus, Rhopalotococcus, Pseudochermes and other genera is discussed.